Comparison of Nephron-protective Effects of Enalapril and GLP Analogues (Exenatide) in Diabetic Nephropathy - Çavusoglu, T.; Erbas, O.; Karadeniz, T.; Akdemir, O.; Acikgoz, E.; Karadeniz, M.; Tuglu, M. I.; Ates, U. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Background: One of the major concerns is a nephropathy in diabetes, which applies many different kinds of medicines. However, required level of the treatment of renal disease has not been achieved.Aim: To investigate and compare the effect of the enalapril and the exenatide on diabetic nephropathy in rats developed diabetes by streptozosin.Material and Methods: 32 male Sprague Dawley rats were divided into 4 groups: (1) Control, (2) Diabetic (DM), (3) DM+ Enalapril, and (4) DM+ exenatide groups. Then, the animals were euthanized and their blood samples were collected by cardiac puncture for blood glucose; blood urea nitrogen (BUN), creatinin, and nephrectomy were performed for histopathologic examination, and urine samples were taken on stick for proteinuria.Results: Administration of the enalapril or the exenatide in diabetic rats resulted in a significant reduction both fibronectin, induced nitric oxide synthase (i-NOS) expression in glomerular area and urine protein levels. It was shown that both of enalapril and exenatide protected the renal glomerulus more than diabetic group in the nephropathy histopathologically.Conclusion: The beneficial effects of enalapril and exenatide which reduces fibronectin, i-NOS expression and urine protein levels or increases recovery of glomerules, might be used for preventing the harmful effects of diabetic nephropathy.
Keywords: medicine; biochemical; histopathological; enalapril; exenatide; diabetes